Effectiveness of cyproheptadine in the prevention of childhood migraine - Zulkarnain Zulkarnain; Johannes Saing; Yazid Dimyati; Bistok Saing (Indonesian Pediatric Society, 2009)
Background Migraine is one of the causes of recurrent headachein childhood. Cyproheptadine is well known as an antihistamine,but there are few studies revealing the drug's effect in pediatricmigraine.Objective To determine the effectiveness of cyproheptadine in the prophylactic treatment of childhood migraine.Methods A randomized placebo-controlled clinical trial studywas performed at Medan. One hundred children with migraineaccording to the International Headache Society criteria wereincluded in the study. Subjects were divided into two groups, andeach group was given either 4 mg cyproheptadine or placebo for 12 weeks. Headache frequency was measured in headache days per month, duration was measured in hours and functional disability was measured by Pediatric Migraine Disability Assessment (PedMID AS). The efficacy was measured before intervention; also 1, 2, and 3 months after intervention.Results A total of 100 patients, with age ranging from 11 to 18 years old (with mean, 15.5 years), were treated with cyproheptadine or placebo for headache. Compared to baseline, there was a significant difference on PedMIDAS grading of migraines in both groups (P<0.05). Headache frequency and duration per month were significantly different after treatment with cyproheptadine (P=0.009, 95% CI 0.001 to 0.030 and P= 0.029, 95% CI 0.690 to 27.510, RR=4.36), compared to placebo group (P> 0.05), but there were side effects of cyproheptadine up to 73%.Conclusion Cyproheptadine appears to be effective as analternative prophylactic treatment of childhood migraine.However, pediatricians should consider the significant side effectsof this drug.